RELATIONSHIP BETWEEN MACRONUTRIENTS INTAKE AND CANCER STAGE WITH BODY MASS INDEX AMONG CANCER PATIENTS ON CHEMOTHERAPY - Puspareni, Luh Desi; Nurrahmah, Putri; Atmaja, Taufiq Firdaus Al-Ghifari (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2025)
Cancer is characterized by the uncontrolled growth and spread of abnormal cells, which can invade and destroy normal body tissue. Body mass index (BMI) is associated with cancer prognosis. Macronutrient intake affects BMI through lipogenesis, muscle formation, and lean body mass. Advanced cancer patients are at risk of malnutrition due to anorexia. The study aims to analyze the association between macronutrient intake and cancer stage with BMI of cancer patients undergoing chemotherapy. The study was used a cross-sectional design. Sampling was used a consecutive sampling technique with a sample size of 50 respondents. Macronutrient intake was collected through 3x24-hour non-consecutive food recalls. Cancer stage data were obtained from patient medical records. Body mass index (BMI) was calculated by dividing body weight (in kilograms) by square of height (in meters). Bivariate analysis used the Spearman-Rank correlation test. The results of the study showed that the median of energy and fat intakes were 1.051 kcal and 35.1 g. The mean of protein and fat intakes were 34.0±11.6 g and 152.4±47.5 g. The mean of energy, fat, and carbohydrate intake percentages were 58.5±17.5%, 70.5±28.6%, and 50.7±17.6%. The median of protein intake percentages was 48,7%. The percentage of energy, protein, and carbohydrate intake was considered a severe deficit, while the percentage of fat intake was considered a moderate deficit. There was association between energy intake and BMI (p-value=0.000; ρ=0.813), protein intake and BMI (p-value=0.000; ρ=0.723), fat intake and BMI (p-value=0.000; ρ=0.607), carbohydrate intake and BMI (p-value=0.000; ρ=0.812), and there was association between cancer stage and BMI (p-value=0.000; ρ=-0.606). It can be concluded that macronutrient intake and cancer stage was related to BMI in cancer patients. Kanker merupakan penyakit yang terjadi karena beberapa sel tumbuh abnormal secara cepat dan bermetastasis ke bagian tubuh lainnya. Indeks massa tubuh (IMT) berhubungan dengan prognosis kanker. Asupan zat gizi makro memengaruhi IMT melalui lipogenesis, pembentukan otot, dan lean body mass. Pasien kanker stadium lanjut berisiko malnutrisi akibat anoreksia. Penelitian ini bertujuan untuk menganalisis hubungan asupan zat gizi makro dan stadium kanker dengan BMI pasien kanker kemoterapi di RSUD KHZ. Musthafa. Penelitian ini menggunakan desain cross-sectional. Pengambilan subjek menggunakan teknik consecutive sampling dengan jumlah sampel 50 responden. Asupan zat gizi makro diperoleh dengan 3x24 hour non-consecutive food recall. Data stadium kanker diperoleh melalui rekam medik pasien. IMT dihitung dengan membagi berat badan (dalam kilogram) dengan tinggi badan yang dipangkat dua (dalam meter). Analisis bivariat menggunakan uji korelasi Spearman-Rank. Hasil penelitian menunjukkan median asupan energi dan lemak adalah 1.051 kkal dan 35,1 g. Rerata asupan protein dan lemak adalah 34,0±11,6 g dan 152,4±47,5 g. Rerata persentase asupan energi, lemak, dan karbohidrat adalah 58,5±17,5%, 70,5±28,6%, dan 50,7±17,6%. Median persentase asupan protein adalah 48,7%. Persentase asupan energi, protein, dan karbohidrat tergolong defisit berat, sedangkan persentase asupan lemak tergolong defisit sedang. Terdapat hubungan antara asupan energi dengan IMT (p-value=0,000; ρ=0,813), asupan protein dengan IMT (p-value=0,000; ρ=0,723), asupan lemak dengan IMT (p-value=0,000; ρ=0,607), asupan karbohidrat dengan IMT (p-value=0,000; ρ=0,812), dan terdapat hubungan antara stadium kanker dengan IMT (p-value=0,000; ρ= -0,606). Dapat disimpulkan bahwa asupan zat gizi makro dan stadium kanker berhubungan dengan IMT pasien kanker.